“KEEPING AN EYE ON ELECTION SECURITY”: A CASE STUDY ON PLAIN LANGUAGE, TRANSPARENCY, DESIGN, AND ELECTORAL TRUST - Brady Moreira Holanda, Gervina; Cappelli, Claudia; Aparecida Corrêa, Joseane; Mendes de Oliveira, Marcela Alves Lopes; da Silva Rodrigues, Rafael; Barbosa Honda e Sousa, Yna (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2026)
This article presents a case study on the use of Plain Language, information design, and collaborative strategies to strengthen transparency and trust in the Brazilian electoral process. The intervention analyzed consisted of producing and distributing posters and leaflets, developed during the 2024 municipal elections, aimed at explaining the security stages of electronic voting in an accessible manner. The chosen methodology was a case study with a mixed-methods approach (quantitative, qualitative, and comparative), including a reaction survey with 121 participants and AI-assisted analysis. Results showed increased perceived clarity (70.2%), recognition of accessible language (78.5%), and a rise in trust in the voting system’s security (81.8%). There was also growth in self-reported ability to explain electoral oversight mechanisms. The comparison with official materials revealed greater readability, organization, and user-centered communication in Plain Language content, without compromising technical rigor. The study concludes that democratizing technical language strengthens democratic legitimacy, providing evidence for public policies against disinformation and replicable models of institutional communication. KEYWORDS: Plain Language. Information Design. Electoral Justice. Transparency. Disinformation.